ANALISIS PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR TERHADAP KINERJA BANK SYARIAH BUMN (Periode 2014-2017) - Mufidhoh, Umrotul; Andriyanto, Irsad; Haerudin, Haerudin (MALIA: Journal of Islamic Banking and Finance, 2017)
This study aimed to analyze empirically the effect of Inflation, Interest Rates, and Exchange Rates on the Profitability  (ROA) of Sharia BUMN Banks in Indonesia for the 2014-2017 Period. The sampling technique used was purposife sampling with the criteria of Sharia State-Owned Banks in Indonesia presenting financial statements for the 2014-2017 period. Data is obtained based on the publication of the Financial Services Authority (OJK ), Bank Indonesia (BI), and the relevant banks for the 2014-2017 period. The sample of this study were 3 Sharia BUMN banks in Indonesia, namely BRISyariah, BNI Syariah and Bank Mandiri Syariah. The analysis technique used is multiple regression with the help of SPSS 21 software. The results showed that inflation, interest rates, and exchange rates did not have a significant effect on ROA. Nevertheless, anticipatory steps need to be prepared so as not to cause problems in the future.Keywords: inflation, interest rate, exchange rate, profitability.